Menjadi Bahagia di Jalan Dao (道): Kebahagiaan Sejati menurut Chuang Tzu (Zhuangzi, 莊子) - Djunatan, Stephanus (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2020)
In the last decade, scientists in almost all disciplines often elaborate happiness using interdisciplinary approaches, metodologies, and measurements, both quantitative and qualitative. Beside scientific approaches, one can also explore this topic from the viewpoint of speculative and phenomenological thinking. This viewpoint describes the experiences of happiness by realising empirical and rational knowledge as well as esoteric consciousness of reality as such. It is Chuang Tzu (Zhuangzi), whose thoughts elaborate cognitive and intuitive sides of human mind, who offers a philosophy in order to bring forward an awareness of reality as itself. Chuang Tzu argues for a realisation of conjunction of both cognitive and intuitive capabilities of human mind, as well as its rational and mystical sides. The realisation of both natural capabilities brings about conditions for modern people’s experience of happiness.